1991
DOI: 10.1002/pssb.2221650111
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Potential Method in the Electronic Theory of Disordered Alloys

Abstract: A general solution of the problem of multiple scattering on a localized random potential is achieved in a single-band model of diagonal disorder for a binary substitutional alloy. A configurationally averaged (T)-matrix is presented as a cluster-type expansion. The short-range order effect on the electronic spectrum, specific heat capacity, and residual electrical conductivity is studied with regard to the multiple scattering on a two-particle cluster (on pairs of atoms) for the coherent potential satisfying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…In particular, the formation of SRO in the alloy is accompanied by a noticeable decrease in the density of electronic states at the Fermi level [27]. The forces of electronic interaction between atoms, determined by the position of the Fermi level in the electron band, will change not only in magnitude but also in sign [18,19,28].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the formation of SRO in the alloy is accompanied by a noticeable decrease in the density of electronic states at the Fermi level [27]. The forces of electronic interaction between atoms, determined by the position of the Fermi level in the electron band, will change not only in magnitude but also in sign [18,19,28].…”
Section: Discussionmentioning
confidence: 99%
“…We take into account the contributions of the scattering processes on pairs of atoms neglecting the contributions of clusters consisting of three and more atoms. In this case, the electronic density of states g(E) per atom can be presented in the form [2] (xY~E, + a m ) arn[(l -x~a i )…”
Section: Theoretical Calculation Of the Electronic Density Of Statesmentioning
confidence: 99%
“…Since the CPA was supposed to fail near the band edges according to [5], it was suggested that this expression can be used to judge the CPA's validity. This criterion was successfully implemented in a series of CPA-based calculations for short-range order alloys [10,11]. Nevertheless, its physical meaning remained quite vague and it was not clear how close one could approach unity and still rely on the CPA results.…”
Section: Introductionmentioning
confidence: 99%